PEMBERDAYAAN PEREMPUAN MISKIN PADA USAHA KECIL DI PERDESAAN MELALUI LAYANAN LEMBAGA KEUANGAN MIKRO - Amelia Maika; Eddy Kiswanto (Populasi, 2007)
This paper will be discussing the service of microfinance agency which had influenced the welfare of poor women who became its clients. The research for this paper took place in Kecamatan Bayat, Klaten, which has been the location of a growing microfinance agency, Mitra Usaha Mandiri (MUM). With the help from this microfinance agency, the poor women were expected to be able to improve their family welfare and gain more income. The easy procedure to apply and its fast process were the keys success of this microfinance agency. The form of this microfinance agency was Grameen Bank model. This model has shown a significant result in many countries. Grameen Bank model put women as their clients because giving credit to women has minor risk compared to men.